Effects of left-hand contraction on tennis serve performance - Mizuno, K.; Masaki, H. (Frontiers in Psychology, 2024)
Introduction: The tennis serve is commonly executed in high-pressure scenarios, often leading to performance decline; a condition commonly referred to as choking under pressure. One suggested effective method to avert choking involves contracting the left hand. We examined the effects of left-hand contraction on tennis serve performance using a wearable grasping material (polyurethane foam) which can be incorporated into sportswear.